Genomics and Prognosis Analysis of Epithelial-Mesenchymal Transition in Glioma - Tao, Chuming; Huang, Kai; Shi, Jin; Hu, Qing; Li, Kuangxun; Zhu, Xingen (Frontiers in Oncology, 2020)
Abstract Background: Glioblastoma is considered to be a brain tumor with highest malignancy. Its high invasiveness and recurrence are obstacles to effective clinical treatment. Moreover, the mechanism of invasion of glioma cells to surrounding brain tissue remains unclear. Epithelial-mesenchymal transition (EMT) has been implicated in the invasion and progression of gliomas. EMT is regulated by induction factors, transcription factor families and an array of pathways that constitute a regulatory network that controls the ability of cancerous cells to penetrate adjacent matrices leading to the deterioration and metastasis of cancer. Methods: We performed a detailed analysis of the expression of EMT-associated induction factors, transcriptional regulators and signaling pathways genes in different grades of gliomas. A prognostic model was constructed to predict overall survival in patients with glioma and was validated in the TCGA data set. Results: We analyzed the differentially expressed 22 common epithelial-mesenchymal transition-associated genes in 508 gliomas graded by different clinicopathological features. Two glioma subgroups (EM1/2) were identified by consistent clustering of the proteins, of which the EM1 subgroup had a better prognosis than the EM2 subgroup, and the EM2 group was associated with cancer migration and proliferation. Significant enrichment analysis revealed that EMT-associated transcriptional regulators and signaling pathways genes were highly related to glioma malignancies. Based on this finding, 7 EMT-related induction factors, transcriptional regulators and signaling pathways genes were used to derive risk scores, which served as independent prognostic markers and prediction factors for the clinicopathological features of glioma. Conclusion: EMT-associated induction factors, transcriptional regulators and signaling pathways genes are important players in the malignant progression of glioma and may help in decision making regarding the choice of prognosis assessment and treatment strategy.